A remarkable structure in a peculiar species of Sarcophagidae (Diptera): description of the male of Lepidodexia (Harpagopyga) albida Lopes - Mello-Patiu, Cátia A. De (Zootaxa, 2015)
The subgenus Harpagopyga Aldrich has 15 nominal species, 14 from the Neotropical Region and one from the Nearctic Region (Pape 1996). The members of this subgenus are recognized by the following combination of characters: row of frontal setae ending level with the base of antenna, ocellar setae not differentiated, arista with plumosity reaching the apex or almost so, proepisternum with few setulae, 3 postsutural dorsocentral and 2 katepisternal setae, postalar wall bare, male midfemur without a ctenidium, phallus with juxta almost right-angled relative to the phallic tube, female tergite 6 well-developed, spermatheca with two differentiated portions (Lopes 1951; Pape 1996).